Sex-specific perceptual adaptations to heat acclimation in highly trained endurance runners - Roberts, R. R.; Keefe, M. S.; Hernandez, M. I.; Dunn, R. A.; Sekiguchi, Y. (International Journal of Exercise Science Conference Proceedings, 2026)
Multiple training sessions in a hot environment (i.e. heat acclimation [HA]) elicit beneficial perceptual adaptations that prepare an individual for future heat stress. However, it remains unclear if high-level male and female endurance athletes respond differently in the magnitude of perceptual adaptation.